Women’s Micro-Enterprises: Factors Influencing Business Performance - Ramli, Ainon; Razali, Zeity Liziana (Archives of Business Research, 2019)
Micro Enterprises have a significant role in contributing to the economic development of Malaysia. However, the enterprises increasingly face competition not only from the same business segment but also from small, medium, and large enterprises. The objective of this study is to analyse the impact of internal and external factors (internal factors: entrepreneurial traits and managerial skills; external factors: access to finance, use of information technology, marketing, availability of business infrastructures) towards women’s micro-business performance in Kelantan, Malaysia. The study adopted a quantitative methodology and surveyed 100 women’s micro-businesses using questionnaires. The study concluded that the internal factors of entrepreneurial traits and managerial skills highly influenced the performance of women’s micro-enterprises. The study further revealed that external factors do not impact the performance of women’s micro-enterprises in Kelantan, Malaysia.